Comparative evaluation of the effectiveness of various intracanal medicaments in eliminating Enterococcus faecalis from simulated internal resorption cavities - Mehmet Çorak; Arzu Kaya Mumcu; Aysel Gülbandılar (Scientific Reports)
Abstract This study aimed to evaluate the antibacterial efficacy of calcium hydroxide (Ca(OH)2), Ca(OH)2 + resveratrol (RV), Ca(OH)2 + silver nanoparticles(AgNPs), and Ca(OH)2 + salicylic acid (SA) against Enterococcus faecalis (E. faecalis) using culture methods and field emission scanning electron microscopy (FE-SEM). Fifty-four extracted single-rooted teeth were prepared with standardized internal resorption cavities and inoculated with E. faecalis (ATCC 29212). After 21 days of incubation, baseline bacterial counts were determined. The teeth were randomly assigned to five groups (n = 10) based on the applied medicament. After 14 days of incubation, bacterial counts were reassessed, and two samples from each group were analyzed using FE-SEM. Data were analyzed using one-way ANOVA and Duncan’s test (p < .05). All medicament groups significantly reduced bacterial counts (p < .001), with Ca(OH)2 + RV, Ca(OH)2 + AgNPs, and Ca(OH)2 + SA demonstrating superior antibacterial activity compared to Ca(OH)2 alone (p < .001). The saline group exhibited the highest bacterial counts (p < .001). Combining Ca(OH)₂ with RV, AgNPs, or SA significantly enhances antibacterial efficacy in internal root resorption cases. These combinations may serve as effective alternatives to Ca(OH)2 alone in endodontic disinfection. Intracanal medicament application plays a vital role in eliminating microorganisms and enhancing the success of endodontic treatment, particularly in cases of internal root resorption. This study highlights the superior antibacterial efficacy of Ca(OH)2 combined with RV, AgNPs, or SA against E. faecalis. These findings suggest that incorporating these adjuncts into intracanal medicaments may improve disinfection outcomes, offering potential clinical benefits in managing internal root resorption cases.